Schnelligkeitsdiagnostik im Mittel- und Langstreckenlauf - eine explorative Faktorenanalyse der deutschen C-Kader-Sportler - Fleckenstein, D. (Leipziger Sportwissenschaftliche Beiträge, 2016)
Performance diagnostics of young elite german middle and long distance runners currently include five testing standards for speed agility: drop jump, countermovement jump, 10 alternate leg bounds, 60 and 100 meter sprint. To understand the relationship between the parameters an explorative factor analysis was conducted. 45 male (18,02 ± 1,36 years) and 36 female (17,62 ± 1,15 years) athletes were included. With regard to complex speed performance, gender differenceswere observed. In contrast to the jumping tests the sprinting tests explained more variance of the structure. High correlations between the sprint tests lead to the suggestion to eliminate the 60 meter sprint.